On the effect specificity of accessory gland products transferred by the love-dart of land snails - Lodi, Monica (BMC Evol Biol, 2016)
BACKGROUND: Sexual selection favours the evolution of male bioactive substances transferred during mating to enhance male reproductive success by affecting female physiology. These effects are mainly well documented for separate-sexed species. In simultaneous hermaphrodites, one of the most peculiar examples of transfer of such substances is via stabbing a so-called love-dart in land snails. This calcareous stylet delivers mucous products produced by accessory glands into the mate’s haemolymph. In Cornu aspersum, this mucus temporarily causes two changes in the recipient. First, the spermatophore uptake into the spermatophore-receiving organ, called diverticulum, is probably favoured by contractions of this organ. Second, the amount of stored sperm increases by contractions of the copulatory canal, which close off the tract leading to the sperm digesting organ. However, it has yet to be determined whether these effects are similar across species, which would imply a common strategy of the dart in increasing male reproductive success. RESULTS: We performed a cross-reactivity test to compare the in vitro response of the diverticulum and copulatory canal of C. aspersum (Helicidae) to its own and other species’ mucus (seven helicids and one bradybaenid). We found that the contractions in the diverticulum were only induced by dart mucus of certain species, while the copulatory canal responded equally to all but one species’ mucus tested. In addition, we report a newly-discovered effect causing the shortening of the diverticulum, which is also only caused by dart mucus of certain species. The advantage seems to be a distance reduction to the sperm storage organ. CONCLUSIONS: All these findings are the first to shed light on the evolution of the different functions of accessory gland products in dart-bearing species. These functions may be achieved via common physiological changes caused by the substances contained in the dart mucus, since the responses evoked were similar across species’ mucus. Moreover, while these substances can act similarly in separate-sexed species as in simultaneous hermaphrodites, differences may occur in their evolution between the two sexual systems. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-016-0672-6) contains supplementary material, which is available to authorized users.